Modern approaches in separation, identification and quantification of polychlorinated biphenyls - Bhaskar Reddy, A.V. (Elsevier B.V., 2020)
Polychlorinated biphenyls (PCBs) are ubiquitous anthropogenic pollutants of major environmental concern. They remain in the environment and disturb the whole ecosystem. Considering the severe toxicity of PCBs on human health and global ecosystem, researchers developed several analytical procedures for the quantification of PCBs from different sources. This review intends to cover latest analytical procedures reported for the analysis of PCBs in different kinds of sample matrices. In particular, advanced sample extraction and clean-up procedures developed with green aspects were highlighted as case studies. The review further addressed the key analytical challenges followed by concluding remarks. Overall, this critical review highlighted all latest technologies reported for the analysis of PCBs. Â© 2020 Elsevier B.V.